Onion thrips, Thrips tabaci (Thysanoptera: Thripidae), reduces yields in indoor-grown cannabis - McCune, Frédéric; Morphy, Chad; Eaves, James; Fournier, Valérie (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2021)
Cannabis (Cannabis sativa L.; Rosales: Cannabaceae) is a newly legalized crop and requires deeper insights on its pest communities. In this preliminary study, we identified a thrips species affecting indoor-grown cannabis in Canada and tested its impact on plant yield. We used three levels of initial infestation (zero, one, and five thrips) on individual plants grown in two growing mediums: conventional substrate or substrate containing the biostimulant Bacillus pumilus Meyer and Gottheil (Bacillales: Bacillaceae). We found that the onion thrips, Thrips tabaci (Lindeman) (Thysanoptera: Thripidae), is proliferating in indoor-grown cannabis. Furthermore, our results showed that fresh yields were higher for the plants that initially received zero thrips compared to those that initially received five thrips. Moreover, the biostimulant only marginally helped reduce the impact of thrips. We highlight the importance for growers to carefully monitor thrips infestations in indoor-grown cannabis. Finally, we emphasize the need for more research related to the impact of pests on cannabis yields and safe means of pest control for this strictly regulated crop.